The Probability Weighting Function - Prelec, Drazen (Econometrica, 1998)
A probability weighting function w(p) is a prominent feature of several nonexpected utility theories, including prospect theory and rank-dependent models. Empirical estimates indicate that w(p) is regressive with respect to the diagonal (w(p) > p for small p, and w(p)